Multimodal Prehabilitation in Major Abdominal Surgery—Rationale, Modalities, Results and Limitations - George Andrei Popescu; Dana Galieta Minca; Nader Mugurel Jafal; Cristian Valentin Toma; Sorin Tiberiu Alexandrescu; Radu Virgil Costea; Catalin Vasilescu (Medicina)
Recent evidence revealed that an adequate preoperative physiological reserve is crucial to overcome surgical stress response. Consequently, a new concept, called prehabilitation, emerged, aiming to improve the preoperative functional reserve of patients who will undergo major abdominal surgery. During the interval between diagnosis and surgery, a multimodal approach consisting of physical exercise and nutritional and psychological support could be employed to enhance physiologic reserve. Physical activity interventions aim to improve aerobic capacity, muscle strength and endurance. Nutritional support addressing malnutrition and sarcopenia also contributes to the achievement of the above-mentioned goals, particularly in patients undergoing cancer-related procedures. Psychological interventions targeting anxiety, depression and self-efficacy, as well as risk behavior modification (e.g., smoking cessation) seem to enhance recovery. However, there is a lack of standardization regarding these interventions, and the evidence about the impact of this multidisciplinary approach on the postoperative outcomes is still contradictory. This narrative review focuses on the physiological basis of surgical stress response and on the efficacy of prehabilitation, reflected mainly in the length of hospitalization and rates of postoperative complications. Multidisciplinary collaboration between surgeons, nutritionists, psychologists and physiotherapists was identified as the key to the success of prehabilitation programs. Synergizing prehabilitation and ERAS protocols significantly improves short-term surgical outcomes. Recent well-designed, randomized clinical trials revealed that this approach not only enhanced functional reserve, but also decreased the rates of postoperative complications and enhanced patient’s overall quality of life, emphasizing the importance of its implementation in routine, elective, surgical care.